A phenomenological approach to Obsessive Compulsive Disorder (2023)
Psychiatry is going through what in current debates has been called “the crisis of psychiatry”. One of the most relevant causes of the crisis of psychiatry has to do with the fact that it has not been successful in approaching psychiatric phenomena from a first-person perspective. Although many approaches to psychiatric phenomena have offered third-person perspectives (the biological/neuro-reductionist, the biopsychosocial, the objective-descriptive, or the values-based model), these perspectives leave aside the way subjects experience or live psychiatric phenomena. Obsessive-Compulsive Disorder has not been alien to this crisis. In this regard, in this Dissertation, I want to offer an understanding of obsessive-compulsive phenomena from a first-person perspective, which is why I draw on phenomenology since it studies the structure of conscious experience. Particularly, I want to offer a description of obsessive-compulsive phenomena at the level of the lived obsessive-compulsive experience. In this respect, I provide an answer to the question: how can obsessive-compulsive phenomena be described at the level of the lived experience? The thesis I defend is that obsessive-compulsive phenomena are a disturbance at the level of existential feelings. This disturbance manifests itself through a feeling of perceptual decoupling that emerges as possibilities for action are not actualized or fulfilled. In obsessive-compulsive experience, the subjects’ world is structured as an uncertain space of possibilities.